Suspected Hand, Foot and Mouth Disease (HFMD) in an Adult: An Uncommon but Important Infectious Disease / Khasnur Abd Malek and Ilham Ameera Ismail - Abd Malek, Khasnur; Ismail, Ilham Ameera (Universiti Teknologi MARA Cawangan Selangor, 2020)
Hand, foot and mouth disease (HFMD) is an uncommon infection to be diagnosed in adults. We present a case of a 32-year-old immunocompetent man with HFMD. This case report highlights the importance of identifying a common childhood disease that could occur in an adult. Recognition is important for possible role in notification, especially for outbreak prevention and to consider potential differential diagnoses. The management and disease prevention measures in a working adult in Malaysia and the shortfalls identified in management guidelines are discussed.